2013
DOI: 10.1158/0008-5472.can-13-1168-t
|View full text |Cite
|
Sign up to set email alerts
|

RHPN2 Drives Mesenchymal Transformation in Malignant Glioma by Triggering RhoA Activation

Abstract: Summary Mesenchymal (MES) transformation is a hallmark of aggressive glioblastoma (GBM). Here we report the development of an unbiased method for computational integration of copy number variation, expression and mutation data from large datasets. Using this method we identified RHPN2 as a central genetic determinant of the MES phenotype of human GBM. Notably, amplification of the human RHPN2 gene on chromosome 19 correlates with a dramatic decrease in the survival of glioma patients. Ectopic expression of RHP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 34 publications
2
56
2
Order By: Relevance
“…Among the genetic alterations reported by the TCGA Consortium (TCGA-Consortium, 2008), only NF1 mutations/deletions were associated with MES-GBM tumors (~25% of samples) (Verhaak et al, 2010) while additional rare mutations and fusion events were recently reported (Danussi et al, 2013; Frattini et al, 2013). Thus, despite multiple studies, the genetic determinants of MES-GBM are still largely elusive and represent an ideal target for the new algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Among the genetic alterations reported by the TCGA Consortium (TCGA-Consortium, 2008), only NF1 mutations/deletions were associated with MES-GBM tumors (~25% of samples) (Verhaak et al, 2010) while additional rare mutations and fusion events were recently reported (Danussi et al, 2013; Frattini et al, 2013). Thus, despite multiple studies, the genetic determinants of MES-GBM are still largely elusive and represent an ideal target for the new algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…However, amplification and overexpression of Rhophilin-2 (RHPN2), another chromosome 19 protein, was recently linked to dramatically decreased survival in glioma patients. 8 In many cancer types, small subsets of tumor-initiating and treatment-resistant cells have been identified. In the cancer stem cell (CSC) hypothesis, stem cells have the capacity to make new tumors and produce progeny cells of many different types.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To further characterize the role of RSF-1 in breast cancer, we analyzed the TCGA gene expression data and identified gene-expression signatures associated with RSF-1 expression levels ((Akavia et al, 2010; Danussi et al, 2013), (Supplementary Methods). Genes associated with RSF-1 in this procedure are putative downstream targets of RSF-1 activity.…”
Section: Resultsmentioning
confidence: 99%